Evaluation of plant diversity and soil-vegetation relationships in some salinity-affected cultivated areas in Egypt - Entesar Abou Glida; Abdel Aziz Mohamed Ragab; Om Mohamed Ahmed Khafagi; Ramadan Bedair (PLoS ONE, 2026)
Soil salinity, characterized by the accumulation of soluble salts, poses a significant global threat to agriculture, affecting over one billion hectares. It induces osmotic stress and ion toxicity, significantly diminishing crop yields and arable land. Egypt, heavily reliant on the Nile Delta, experiences severe salinization resulting from irrigation practices, climate change, and inherent aridity. This escalating crisis compromises agricultural productivity and food security, necessitating urgent global solutions. A total of 103 plant taxa were documented. Asteraceae (22 species) and Poaceae (13 species) constituted the most diverse families. Annuals (50.0%) and therophytes (49.5%) represented the predominant life forms, while biregional species (36.9%) formed the largest chorological group. Soil physicochemical properties, including particle size distribution, pH, EC, TDS, organic matter, saturation percentage, SAR, available N, P, and K, major ions (Ca² ⁺ , Mg² ⁺ , Na ⁺ , K ⁺ , Cl ⁻ , HCO₃ ⁻ , SO₄²⁻), and CaCO₃%, were determined in all stands. Two-Way Indicator Species Analysis (TWINSPAN) and Detrended Correspondence Analysis (DCA) classified the studied stands into six distinct groups. Stands within each group exhibited ecological similarity. Each vegetation group possessed its own set of indicator plant species, and the soil factors most closely associated with them.